Sustainable production of graphene oxide with ascorbic acid reduction: characterization and insights - Thaddeus Lee; Chun Hui Tan; Chai Yan Ng; Hing Wah Lee; Chun Hong Voon; Foo Wah Low (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
In this study, graphene oxide (GO) was synthesized from graphite powder using KMnO4 and a concentrated mixture of H2SO4/H3PO4. The obtained GO was subsequently reduced using ascorbic acid. The ratios of H2SO4 to H3PO4 and KMnO4 to graphite powder were kept constant. The synthesized GO and reduced graphene oxide (rGO) were evaluated using UV-visible spectroscopy, FT-IR spectroscopy, XRD, SEM, and EDX. The findings showed that processing graphite powder with KMnO4 at 60 °C for 12 hours resulted in a high degree of oxidation and minimal defects. Furthermore, ascorbic acid, an alternative to highly toxic hydrazine, aided in eliminating oxygen-containing functional groups in the rGO. This study focuses on the properties of GO produced using the improved Hummer’s method, and the changes observed after chemical reduction.